Autonomous metrology for robot mounted 3D vision systems. Issue 1 (2017) - Kinnell, Peter; Rymer, Tom; Hodgson, John; Justham, Laura; Jackson, Mike
Abstract: Using a metrology system simulation approach, an algorithm is presented to determine the best position for a robot mounted 3D vision system. Point cloud data is simulated, taking into account sensor performance, to create a ranked list of the best camera positions. These can be used by a robot to autonomously determine the most advantageous camera position for locating a target object. The algorithm is applied to an Ensenso active stereo 3D camera. Results show that when used in combination with a RANSAC object recognition algorithm, it increased positional precision by two orders of magnitude, from worst to best case.